The Relationship between Academic Persistence and Student Achievement in Chemistry and Its Implications for Curriculum Development: Hubungan Kegigihan Akademik dengan Prestasi Mahasiswa Kimia dan Implikasinya terhadap Pengembangan Kurikulum - Joseph Rezeki Hulu; Ifan Rivaldo; Yerimadesi Yerimadesi; Afifah Nur Hasanah; Dwinita Sahalina (IAIN Sorong, 2026)
Student achievement is an important indicator in assessing the quality of higher education, but this achievement still shows significant variation, indicating the influence of internal student factors. One non-cognitive factor suspected to play a role is academic persistence, namely the ability to maintain effort and consistency in achieving long-term goals. This study aims to analyze the relationship between academic persistence and student achievement and its implications for curriculum development. The study used a quantitative approach with a survey. Participants were 192 undergraduate students in Chemistry Education and Chemistry Science at Padang State University, selected using stratified random sampling. Data were collected using a Likert-scale questionnaire to measure academic persistence and documented GPA as an indicator of achievement. Data analysis included validity, reliability, and normality tests, as well as Pearson correlation and simple linear regression. The results showed that the instrument had good validity and high reliability, with a Cronbach's Alpha value of 0.784. The normality test indicated that the data were normally distributed (p = 0.071). The results of the correlation analysis indicate a strong and significant positive relationship between academic persistence and student achievement (r = 0.780; p < 0.05). The regression results show a coefficient of determination (R²) of 0.609, which means that academic persistence contributes 60.9% to the variation in student achievement. This finding indicates that the higher the academic persistence, the higher the student achievement. The implications of this study emphasize integrating non-cognitive character strengthening into curriculum development. This can be realized through Project-Based Learning, process-based assessment, lecturers as facilitators providing constructive feedback, and supporting programs such as growth mindset training, academic mentoring, and stress management to produce graduates who are academically strong and resilient.